Intangibles, Market Failure and Innovation Performance - Bounfour, Ahmed; Miyagawa, Tsutomu (Springer International Publishing : Imprint: Springer, 2015)
This book addresses the issue of intangibles' contribution to growth at macroeconomic and microeconomic levels. It provides a review of a set of new approaches to innovation growth. It also considers the issue of how to invest in intangibles, especially with regard to the market failure issue. The book focusses on three major themes: First it provides a better understanding of how intangibles contribute to economic growth and value creation. In a second part it presents emerging practices as well as examples of market failure, analyzing managerial practices in relationship to market imperfections. Finally the book links the value of intangibles with innovation and the performance of firms.